2003
DOI: 10.1093/icb/43.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Vision and Its Role in Biological Signaling

Abstract: Visual pigments, the molecules in photoreceptors that initiate the process of vision, are inherently dichroic, differentially absorbing light according to its axis of polarization. Many animals have taken advantage of this property to build receptor systems capable of analyzing the polarization of incoming light, as polarized light is abundant in natural scenes (commonly being produced by scattering or reflection). Such polarization sensitivity has long been associated with behavioral tasks like orientation or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 60 publications
0
140
0
Order By: Relevance
“…Though the signalto-noise ratio is low at lower Sun elevations, high polarization sensitivity may help to overcome this limitation [16]. Hence, we expect that polarization cues, under the specific conditions mentioned above, could be used by marine animals for navigation (e.g.…”
Section: Results (A) Stability Of the Per Cent Polarization Phase Funmentioning
confidence: 99%
“…Though the signalto-noise ratio is low at lower Sun elevations, high polarization sensitivity may help to overcome this limitation [16]. Hence, we expect that polarization cues, under the specific conditions mentioned above, could be used by marine animals for navigation (e.g.…”
Section: Results (A) Stability Of the Per Cent Polarization Phase Funmentioning
confidence: 99%
“…Motivated by polarization sensitivity in marine animals, 3,[17][18][19][20] it has recently been shown that underwater path radiance can be compensated for 12 by analysis of polarization-filtered images. Therefore, some of the problems addressed in the current paper with regard to haze may apply underwater, or in other media.…”
Section: Discussionmentioning
confidence: 99%
“…Among them is the ability to detect the direction of the electric field component (e-vector) of linearly polarized light (see Labhart 2006 andHorvĂĄth andVarjĂș 2004 for recent reviews). This ability can be used for orientation (Wehner 1992;von Frisch 1967), the detection of water surfaces (Horvath and Varju 1997;Schwind 1991), and in communication (Cronin et al 2003;Marshall et al 1999). A specialized region for polarized vision exists in the dorsal rim area of most compound eyes.…”
Section: Basic Functional Diversitymentioning
confidence: 99%